THE INFLUENCE OF MATERNAL NUTRITION ON THE DEVELOPMENT OF AUTISM SPECTRUM DISORDER: A LITERATURE REVIEW (REMUNOM, 2025)
This study is a literature review that investigated the relationship between maternal nutrition during pregnancy and the risk of Autism Spectrum Disorder (ASD). Studies published in the last 10 years, available in English, Portuguese, or Spanish, that address the proposed theme were included. The search was conducted in the PubMed, Scopus, SciELO, and LILACS databases using controlled descriptors. The findings show that the nutritional status of pregnant women plays a relevant role in fetal neurodevelopment and may influence the risk of alterations associated with ASD. Despite the promising evidence, more robust studies are still needed to confirm the causality of these relationships. Thus, individualized prenatal nutritional monitoring integrated with other areas of health is recommended, aiming to promote healthier brain development and reduce the risk of ASD.